Competitiveness and innovation of the Polish food industry - Krzysztof FIRLEJ; Anna KOWALSKA; Arkadiusz PIWOWAR (Agricultural Economics (AGRICECON), 2017)
Agribusiness is the biggest production sector in the European Union taking into account both the value of turnover and the creation of added value as well as employment size. In this context, the food industry deserves a special distinction. In the publication, the analyses of the food industry competitiveness in Poland are presented. For analysing and assessing competitiveness of the Polish food industry, the following factors were used: the orientation of export (OE), covering of import by export (TC), the import penetration (MP) and the revealed comparative advantages according to the Balassa (RCA) and Lafay (LFI). The study also presents the findings of empirical research on an innovative character of the food industry in Poland.